2020
DOI: 10.3390/nu12041037
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Action of Prebiotics and Their Effects on Gastro-Intestinal Disorders in Adults

Abstract: In recent years, research has focused on the use of dietary fibers and prebiotics, since many of these polysaccharides can be metabolized by intestinal microbiota, leading to the production of short-chain fatty acids. The metabolites of prebiotic fermentation also show anti-inflammatory and immunomodulatory capabilities, suggesting an interesting role in the treatment of several pathological conditions. Galacto-oligosaccharide and short-and long-chain fructans (Fructo-oligosaccharides and inulin) are the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(116 citation statements)
references
References 157 publications
(242 reference statements)
1
110
0
5
Order By: Relevance
“…The mechanism of probiotic efficacy is supposed to be connected with the impact on the gut microbiota and its metabolome and with a direct activation of the gut associated lymphoid tissue as well as a modification of the microbiome-gut-brain axis. However, prebiotic oligosaccharides also play an important role in modulation of the intestinal microbiota and are the main source of short chain fatty acids such as acetate, propionate and butyrate [ 34 ]. Recent analyses of the gut microbiota of IBS patients have shown that microbial dysbiosis in IBS depends on IBS subtypes, and IBS-D but not IBS-C is characterized by a reduction of butyrate producing bacteria such as Ruminococcaeae , unknown Clostridiales and Erisipelotrichaceae [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of probiotic efficacy is supposed to be connected with the impact on the gut microbiota and its metabolome and with a direct activation of the gut associated lymphoid tissue as well as a modification of the microbiome-gut-brain axis. However, prebiotic oligosaccharides also play an important role in modulation of the intestinal microbiota and are the main source of short chain fatty acids such as acetate, propionate and butyrate [ 34 ]. Recent analyses of the gut microbiota of IBS patients have shown that microbial dysbiosis in IBS depends on IBS subtypes, and IBS-D but not IBS-C is characterized by a reduction of butyrate producing bacteria such as Ruminococcaeae , unknown Clostridiales and Erisipelotrichaceae [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, prebiotic-derived SCFAs also stimulate the immune system and exert anti-inflammatory activities by inhibiting NFKB pathway, reinforcing the defense of the individuals and reducing the development of allergic and inflammatory diseases ( 36 ). The mechanisms of action of prebiotics at molecular and cellular level were the subject of several recent reviews ( 37 , 38 ). However, it is important to state that soluble dietary fiber can also exert physiological effects through mechanisms independent of their prebiotic effects.…”
Section: The Concept Of “Prebiotics”mentioning
confidence: 99%
“…In healthy individuals, it was observed that the bifidogenic effect of prebiotics is dose-dependent and the minimum dose required may vary depending on the type of prebiotic. While for FOS it seems the minimum dose is 10 g/day, for inulin, a lower dose seems to be enough (2.5–5 g/day) [ 61 ]. As far as we know, there is no study in CKD that evaluated the dose–response effect of prebiotics on the serum level of uremic toxins.…”
Section: Discussionmentioning
confidence: 99%